EXTH-104. ROLE OF CLPP AND MITOCHONDRIAL METABOLISM IN THE ANTI-CANCER EFFECTS OF IMIPRIDONE ONC201 AND ONC206 IN GLIOBLASTOMA AND DIPG. (14th November 2022) - Foster, Scott; Lee, Andrew; Maranto, Cristina; Allen, Joshua E; Lanier, Randall; Sethna, Phiroze; Prabhu, Varun V
Abstract: ONC201 is the first bitopic dopamine receptor D2 (DRD2) antagonist and allosteric mitochondrial protease ClpP agonist. ONC201 is well tolerated and induces durable tumor regressions in H3 K27M-mutant glioma patients. ONC206, a derivative of ONC201 currently in Phase I trials, is also a bitopic DRD2 antagonist and ClpP agonist with enhanced nanomolar potency relative to ONC201. We evaluated in vitro efficacy, mechanism(s) of action and acquired resistance for ONC201 and ONC206 in glioblastoma (GBM) (T98G, A172, U87MG), H3.3 K27M mutant DIPG (SF8628, SF7761) and astrocytoma (H4, U118MG) cell lines. ONC206 was more potent than ONC201 in cell viability assays for all line. A mutation in ClpP has previously been associated with resistance to imipridones. Accordingly, SF8628 cells with a CRISPR-mediated ClpP knockout were resistant to both ONC201 and ONC206. Polyclonal resistant cell lines were generated through prolonged passaging in increasing concentrations of ONC201 (SF8628 and T98G cells) or ONC206 (T98G cells). Cells with acquired resistance to ONC201 (ONC201Res) or ONC206 (ONC206Res) showed cross resistance to both imipridones. Time-stability of resistance was confirmed by removing drug for 2 to 4 weeks and retesting. Whole genome sequencing revealed ClpP mutations in both ONC201Res and ONC206Res T98G cells. RNAseq analysis revealed upregulation of the integrated stress response, apoptosis pathways, and amino acid metabolism with imipridone treatment in T98G parental cells but not resistant clones. Depleting glucose in the media enhanced cell viability inhibition by imipridones, indicating mitochondrial metabolism may contribute to their mechanism of action. Our results identify ClpP and mitochondrial metabolism as key aspects for the mechanism of action of ONC201 and ON206 in DIPG and GBM cell lines.